Metabolite profiling of tartary buckwheat-an underutilized neutraceutical crop of Kashmir Himalaya - Pirzadah, Tanveer Bilal; Malik, Bisma; Tahir, Inayatullah; Rehman, Reiaz Ul (Journal of Phytology, 2017)
The aim of the present study was to explore the possible metabolites in the methanolic extract of root, stem, groat and hull of the neutraceutical crop, Fagopyrum tataricum using GC-MS technique. From GC-MS metabolite profiling, over 90 different metabolites were identified among root, stem, groat and hull extract.Â The most prevailing compounds were 3, 3â€™, 4â€™, 5, 7-pentahydroflavone-3-rhamnoglucoside (71.94%) in groat, 9, 12-octadecadienoic acid (49.38%) in root, 6-octadecanoic acid, a steric acid (70.46%) in hull and Cis-9-hexadecanal (13.38%) in stem. Present investigation reveals that F. tataricum is an excellent source of many metabolites such as, fatty acids, hydrocarbons, steroids, terpenoids, esters, organic acids and aldehydes with excellent pharmaceutical properties. These results suggest that tartary buckwheat could be a promising alternative in the functional food sector and neutraceutical to improve social well-being and diminish malnutrition.